Low-cost Software-Defined Radio System with Deterministic RX to TX Delay Using Timestamps - Dorn, Christian; Depold, Andreas; Lurz, Fabian; Hagelauer, Amelie (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
Systems that rely on high-level software share the same disadvantage. Their execution time is unknown and thus the result of the processing is not available after a deterministic delay. The same is valid for software-defined radios. When only in receive (RX) mode the impact of the varying delay is negligible most of the time. However, in the case that the SDR needs to transmit (TX) this delay prevents from synchronizing the TX to the RX. This is crucial for many applications in communication and sensing though. This publication proposes and implements a method on a low-cost SDR transceiver, that provides the possibility to TX at a given time related to the RX with an error of ±l sample.
CRIS-Team Scopus Importer:2023-03-17
Keywords: software-defined radio (SDR); time synchronization